Pengaruh Pupuk Biomi Dan Urea Terhadap Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L) - I Nyoman Wisnu Semarajaya; Made Sri Yuliartini; I Gusti Bagus Udayana; A.A Ngurah Mayun Wirajaya (Fakultas Pertanian, Universitas Warmadewa, 2020)
This research is a field experiment conducted in paddy fields in Sumerta Village, East Denpasar District, with a place height of 40 meters above sea level, with an average temperature of 25-30 oC, which was carried out from 1 May 2018 to 4 June 2018. The purpose of this study was to find the influence of the concentration of liquid organic fertilizer biomi with urea fertilizer on the growth and yield of mustard plants. This experiment used a randomized block design (RBD) with a factorial pattern, which consisted of two factors, namely: the concentration of liquid organic fertilizer biomi (B) and urea (U). The first factor, the concentration of liquid organic fertilizer biomi (B) consists of 4 levels: B0 = (0 ml l-1), B1 = (2.5 ml l-1), B2 = (5 ml l-1), B3 = (7.5 ml l-1). The second factor, the dose of urea (U) consists of 2 levels: U0 = (0 kg ha-1), U1 = (50 kg ha-1). Based on the results of this study, we can conclude the following: the interaction of liquid organic fertilizer dose biomi with urea fertilizer has no significant effect on all observed variables. The administration of 50 kg ha-1 urea fertilizer (U1) gave the fresh weight of the crop per plant ie 99.85 g, increasing by 28.57% compared to without urea fertilizer. The treatment of liquid organic fertilizer biomi concentration of 7.5 ml l-1 (B3) gave the highest yield that can be seen from the highest fresh weight of the crop which and the highest weight of the economic yield is 93.63 g and 80.90 g